Sex-based utilization of guideline recommended statin therapy and cardiovascular disease outcomes: Data from a multisite healthcare network primary prevention cohort - Agnes Koczo; Adipong Brickshawana; Jianhui Zhu; Floyd Thoma; Malamo Countouris; Kathryn Berlacher; Martha Gulati; Erin D Michos; Steven Reis; Suresh Mulukutla; Anum Saeed (Elsevier, 2024)
Background: In the US, women have similar cardiovascular death rates as men. However, less is known about sex differences in statin use for primary prevention and associated atherosclerotic cardiovascular disease (ASCVD) outcomes. Methods: Statin prescriptions using electronic health records were examined in patients without ASCVD (myocardial infarction (MI), revascularization or ischemic stroke) between 2013 and 2019. Guideline-directed statin intensity (GDSI) at index (at least moderate intensity, defined per pooled-cohort equation) and follow-up visits were compared between sexes across ASCVD risk groups, defined by the pooled-cohort equation. Cox regression hazard ratios were calculated for statin use and outcomes (myocardial infarction, stroke/transient ischemic attack (TIA), and all-cause mortality) stratified by sex. Interaction terms (statin and sex) were applied. Results: Among 282,298 patients, (mean age ∼ 50 years) 17.1 % women and 19.5 % men were prescribed any statin at index visit. Time to GDSI was similar between sexes, but the proportion of high-risk women on GDSI at follow-up were lower compared to high-risk men (2-years: 27.7 vs 32.0 %, and 5-years: 47.2 vs 55.2 %, p < 0.05). When compared to GDSI, no statin use was associated with higher risk of MI and ischemic stroke/TIA among both sexes. High-risk women on GDSI had a lower risk of mortality (HR=1.39 [1.22-1.59]) vs. men (HR=1.67 [1.50-1.86]) of similar risk (p value interaction=0.004). Conclusion: In a large contemporary healthcare system, there was underutilization of statins across both sexes in primary prevention. High-risk women were less likely to remain on GDSI compared to high-risk men. GDSI significantly improved the survival in both sexes regardless of ASCVD risk group. Future strategies to ensure continued use of GDSI, specifically among women, should be explored.